Tooth loss after active periodontal therapy. 1: patient-related factors for risk, prognosis, and quality of outcome - Peter Eickholz (Blackwell Synergy, 2008)
Objectives: Assessment of patient-related factors contributing (1) to tooth loss and (2) to the quality of treatment outcome 10 years after initiation of anti-infective therapy. Material and Methods: All patients who had received active periodontal treatment 10 years ago by the same examiner were recruited consecutively until a total of 100 patients were re-examined. Re-examination was performed by a second examiner and included clinical examination, test for interleukin-1 (IL-1) polymorphism, smoking history, review of patients’ files (e.g. regularity of supportive periodontal therapy: SPT). Statistical analysis included Poisson and logistic regressions. Results: Fifty-three patients attended SPT regularly, 59 were females, 38 were IL-1 positive. Poisson regressions identified mean plaque index during SPT (po0.0001), irregular attendance of SPT (po0.0001), age (po0.0001), initial diagnosis (p50.0005), IL-1 polymorphism (p50.0007), smoking (p50.0053), and sex (p50.0487) as factors significantly contributing to tooth loss. Additionally, mean plaque index during SPT (p50.011) and irregular SPT (p50.002) were associated with a worse periodontal status 10 years after initiation of therapy. Conclusion: The following risk factors for tooth loss were identified: ineffective oral hygiene, irregular SPT, IL-1 polymorphism, initial diagnosis, smoking, age and sex.